Does Gender Moderate the Relationship Between Chronic Pain and Substance Use Disorder? Insights From a National Canadian Population Survey - Su, Yingying; Meng, Xiangfei; D'Arcy, Carl (Frontiers in Psychiatry, 2022)
Background: Though it has been shown that men have a higher lifetime prevalence of substance use disorder and a lower prevalence of chronic pain than women, there is little research to date focusing on gender differences in the relationship between chronic pain and substance use disorder. This study examined whether gender moderates the relationship of chronic pain and substance use disorder. We also sought to examine the gender differences in the associations between specific pain types - arthritis, migraine and back pain, and substance use disorder. Methods: The data were drawn from the 2012 Canadian Community Health Survey-Mental Health (CCHS-MH 2012) with individuals aged 20 years and older living in the ten Canadian provinces (N = 23,089). A two-level logistic mixed effects model was used to account for provincial differences. Results: Our findings indicated gender moderated the association between arthritis as well as migraine, and substance use disorder. However, no moderation effect of gender on the relationship between back pain and substance use disorder was found. Specifically, the strength of the association between arthritis and substance use disorder was stronger among men (ORinteraction=0.62, 95%CI: 0.53 to 0.73), whereas the strength of the association between migraine and substance use disorder was stronger among women (ORinteraction=1.45, 95%CI: 1.18 to 1.79). In addition, geographical location was found to explain a small proportion (2.3%-2.4%) of the overall variance in SUD. Conclusions: The results suggest that gender moderated the relations between arthritis as well as migraine, and substance use disorder, respectively. Treatment programs for pain and substance misuse might benefit from an approach tailored to gender differences.